The Effect of High-Definition Transcranial Direct Current Stimulation of the Right Inferior Frontal Gyrus on Empathy in Healthy Individuals - Wu, Xiaoling; Xu, Feifei; Chen, Xingui; Wang, Lu; Huang, Wanling; Wan, Ke; Ji, Gong-Jun; Xiao, Guixian; Xu, Sheng; Yu, Fengqiong; Zhu, Chunyan; Xi, Chunhua; et al. (Frontiers in Human Neuroscience, 2018)
Empathy, including cognitive and emotional empathy, refers to the ability to infer the mental states of others and to the capacity to share emotions. The neural mechanisms involved in empathy are complex and not yet fully understood, and previous studies have shown that both cognitive and emotional empathy are closely associated with the inferior frontal gyrus (IFG). In this study, we examined whether empathy can be modulated by high-definition transcranial direct current stimulation (HD-tDCS) of the right IFG. Twenty-three healthy participants took part in all three experimental conditions (i.e., anodal, cathodal and sham stimulation) in a randomized order. Participants then completed the Chinese version of the Multifaceted Empathy Test (MET), which assesses both cognitive and emotional empathy. The results show that scores obtained for cognitive empathy following cathodal stimulation are significantly lower than those obtained following sham stimulation. In addition, scores obtained for cognitive empathy following anodal stimulation are higher than those obtained following sham stimulation, though the difference is only marginally significant. However, the results fail to show whether the stimulation of the right IFG via HD-tDCS plays a role in emotional empathy. Our results suggest that the right IFG plays a key role in cognitive empathy and indicate that HD-tDCS can regulate cognitive empathy by inducing excitability changes in the right IFG.